Volleyball Underhand Passing Learning Model based on Teaching Games for Understanding (TGfU) for Elementary School Students - Agus Parman; Ilham; Tri Bayu Norito; Ugi Nugraha; Hendri Munar; Alek Oktadinata (Universitas Pendidikan Ganesha, 2026)
Physical education learning often focuses solely on mastering techniques without engaging students in understanding the concepts of the game, resulting in low participation and limited comprehension of the learning activities. This study aims to develop a Student Worksheet (LKPD) based on the Teaching Games for Understanding (TGfU) learning model for the underhand passing technique in volleyball for elementary school students. The research was conducted at SDN 80/I Muara Bulian, Batanghari Regency, Jambi Province. The study employed a research and development (R&D) approach using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Expert validation results indicated a very high level of feasibility, with an average score of 4.3 or 86%. The small-group trial achieved an average score of 4.27 or 85.3%, while the large-group trial obtained 4.25 or 85%, both categorized as very good. Teacher and student responses were also very positive, at 88% and 86.6%, respectively. These findings demonstrate that the developed LKPD is not only valid in content but also practical and effective in supporting the learning process. It is concluded that the TGfU-based LKPD is a feasible and innovative learning medium that enhances conceptual understanding, underhand passing skills, and students’ learning motivation. The implications of this study suggest that TGfU-based LKPD can serve as an alternative learning medium that promotes active, contextual, and enjoyable physical education learning in elementary schools.